2016
DOI: 10.1063/1.4951675
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid slip flow over a stretching cylinder with Schmidt and Péclet number effects

Abstract: A mathematical model is presented for three-dimensional unsteady boundary layer slip flow of Newtonian nanofluids containing gyrotactic microorganisms over a stretching cylinder. Both hydrodynamic and thermal slips are included. By applying suitable similarity transformations, the governing equations are transformed into a set of nonlinear ordinary differential equations with appropriate boundary conditions. The transformed nonlinear ordinary differential boundary value problem is then solved using the Runge-K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…A similar response has been observed by Basir et al (2016). Physically, as the thermal slip parameter rises, the fluid flow within the boundary layer becomes progressively less sensitive to the heating effects at the cone surface and a decreased quantity of thermal energy (heat) is transferred from the hot cone surface to the fluid, resulting in a fall in temperatures, manifesting in a cooling and thinning of the thermal boundary layer.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…A similar response has been observed by Basir et al (2016). Physically, as the thermal slip parameter rises, the fluid flow within the boundary layer becomes progressively less sensitive to the heating effects at the cone surface and a decreased quantity of thermal energy (heat) is transferred from the hot cone surface to the fluid, resulting in a fall in temperatures, manifesting in a cooling and thinning of the thermal boundary layer.…”
Section: Resultssupporting
confidence: 74%
“…decelerates the flow) and cools the regime. Basir et al (2016) considered transient nanofluid bioconvection boundary layer flow from a stretching horizontal cylinder with four slip mechanisms-thermal, velocity, nanoparticle mass and micro-organism slip. Prasad et al (2013) obtained finite difference solutions for nonlinear heat and momentum transfer from a sphere in Darcy -Forchheimer porous media with velocity and thermal slip effects.…”
Section: Introductionmentioning
confidence: 99%
“…Basir et al [15] examined multiple slip effects in nanofluid enrobing flow from an extending cylindrical body with Maple software. Hamad and Ferdows [16] studied heat sink/source and wall transpiration effects on stagnation point nanofluid flow from a stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…These include Ali et al (thermal polymer processing), Bég et al (magnetic materials processing with cross‐diffusion), Abel et al (time‐dependent nonisothermal hydromagnetic extrusion flows), Ahmad et al (variable thermal conductivity stretching thermal flow), Gupta et al (unsteady micropolar sheet stretching with wall suction), Yam et al (rheological flow from stretching wedge geometries), Uddin et al (high‐temperature nanofluid boundary layer slip flows from extending/contracting sheets). Further numerical studies include Sajid et al (Newtonian viscous flow from curved stretching sheets), Latiff et al (time‐dependent micropolar nanofluid biological slip flows from shrinking or contracting sheets), Hayat et al viscous thermosolutal transport from oblique extending cylindrical bodies), Bég et al gyrotactic nanobioconvection fully developed flow in stretching/shrinking microchannels, Ali (transpiring heat transfer from a stretched sheet) and Basir et al (external transient axisymmetric nanobioconvection slip boundary layers from a stretching pipe). In these studies, different models for stretching were utilized including linear, quadratic, exponential and also power‐law and it was shown that stretch rates have a significant influence on skin friction and heat and mass transfer rates at the wall.…”
Section: Introductionmentioning
confidence: 99%